2020
DOI: 10.3390/ijms21041453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Orally Administered Resveratrol on TNF, IL-1β, Leukocyte Phagocytic Activity and Oxidative Burst Function in Horses: A Prospective, Randomized, Double-Blinded, Placebo-Controlled Study

Abstract: Resveratrol, a phytophenol, is a commonly used equine nutraceutical supplement touted to exert anti-inflammatory effects. The effect of orally administered resveratrol on tumor necrosis factor (TNF), interleukin-1β (IL-1β), leukocyte phagocytic activity or oxidative burst function have not been reported in horses. The objective of this study was to determine the effects of a commercially available, orally administered resveratrol product on innate immune functions in healthy adult horses. Whole blood was colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Shang et al report that resveratrol is protective in LPS-induced cardiomyopathy in rats also through inhibition of NFκB (104). In horses, however, Martin et al showed that a 3 week course of resveratrol did not increase antimicrobial function or alter cytokine release profiles of ex vivo stimulated leukocytes (105).…”
Section: Natural Products That Induce Mitochondrial Biogenesismentioning
confidence: 99%
“…Shang et al report that resveratrol is protective in LPS-induced cardiomyopathy in rats also through inhibition of NFκB (104). In horses, however, Martin et al showed that a 3 week course of resveratrol did not increase antimicrobial function or alter cytokine release profiles of ex vivo stimulated leukocytes (105).…”
Section: Natural Products That Induce Mitochondrial Biogenesismentioning
confidence: 99%